Hempseed increases gamma-tocopherol in egg yolks and the breaking strength of tibias in laying hens - Skřivan, Miloš; Englmaierová, Michaela; Vít, Tomáš; Skřivanová, Eva (PloS one, 2019)
The effect of hempseed in the diet of laying hens was evaluated at 0, 30, 60 and 90 g/kg concentrations. The aim of the study was to determine the effect of dietary treatment on the performance of hens, the physical characteristics of egg quality, the concentrations of α- and γ-tocopherol and the carotenoid and cholesterol contents of egg yolks, together with the breaking strength of tibial measurements. In light of the obtained results, our study aimed to address the optimal dietary level of hempseed in laying hen diets. Lohmann Brown hens (n = 240) were divided into 4 dietary treatment groups (6 cages per treatment) with 10 hens per cage. The experiment lasted for 12 weeks. The level of nutrients in all diets (wheat-corn) was well balanced. The dietary metabolisable energy was adjusted using rapeseed oil. The addition of 30 g/kg of hempseed to the diet significantly increased (P˂0.001) egg production and egg mass. Alpha-tocopherol increased significantly (P = 0.002) only in the case of the 60 g/kg hempseed level (101 mg/kg dry matter (DM) versus 83 mg/ kg DM in the control group). In contrast, the level of γ-tocopherol increased gradually from 11 mg/kg DM in the control to 29, 39 and 43 mg/kg DM at the 30, 60 and 90 g/kg levels of dietary hempseed, respectively. The concentrations of beta carotene, zeaxanthin and lutein in egg yolks were not influenced by the dietary treatment. Hempseed at 90 g/kg (P = 0.036) decreased egg shell thickness without affecting its strength. The addition of hempseed decreased (P˂0.001) the cholesterol concentration in the egg yolks in all experimental groups. The addition of 30, 60 and 90 g hempseed increased (P˂0.001) the breaking strength of the tibia to 354, 352 and 350 N, respectively, compared to 297 N in the control group. The highest level of hempseed in the diet positively influenced the Ca concentration in the tibia (P = 0.021). The concentration of P in the tibia was negatively affected in the 60 to 90 g/kg hempseed treatments (P˂0.001). Eggs are a significant source of α-tocopherol. Based on our results, there is a possibility for enrichment of egg yolks with γ-tocopherol, with all of its associated health benefits, by the addition of hempseed to the diet of laying hens. Another significant benefit of hempseed is its effect on the breaking strength of the tibia, which can help with crucial problems in the commercial breeding of laying hens.
Keywords: Cannabis; Egg Yolk; Female; gama-tokoferol; Animal Feed; kur domácí; Animals; Seeds; ženské pohlaví; gamma-Tocopherol; vaječný žloutek; krmivo pro zvířata; Chickens; zvířata; Tibia; semena rostlinná; tibie